Comparative analysis of Campylobacter isolates from wild birds and chickens using MALDI-TOF MS, biochemical testing, and DNA sequencing. (May 2018) - Lawton, Samantha J.; Weis, Allison M.; Byrne, Barbara A.; Fritz, Heather; Taff, Conor C.; Townsend, Andrea K.; Weimer, Bart C.; Mete, Aslı; Wheeler, Sarah; Boyce, Walter M.
Matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS) was compared to conventional biochemical testing methods and nucleic acid analyses (16S rDNA sequencing, hippurate hydrolysis gene testing, whole genome sequencing [WGS]) for species identification of Campylobacter isolates obtained from chickens ( Gallus gallus domesticus, n = 8), American crows ( Corvus brachyrhynchos, n = 17), a mallard duck ( Anas platyrhynchos, n = 1), and a western scrub-jay ( Aphelocoma californica, n = 1). The test results for all 27 isolates were in 100% agreement between MALDI-TOF MS, the combined results of 16S rDNA sequencing, and the hippurate hydrolysis gene PCR ( p = 0.0027, kappa = 1). Likewise, the identifications derived from WGS from a subset of 14 isolates were in 100% agreement with the MALDI-TOF MS identification. In contrast, biochemical testing misclassified 5 isolates of C. jejuni as C. coli, and 16S rDNA sequencing alone was not able to differentiate between C. coli and C. jejuni for 11 sequences ( p = 0.1573, kappa = 0.0857) when compared to MALDI-TOF MS and WGS. No agreement was observed between MALDI-TOF MS dendrograms and the phylogenetic relationships revealed by rDNA sequencing or WGS. Our results confirm that MALDI-TOF MS is a fast and reliable method for identifying Campylobacter isolates to the species level from wild birds and chickens, but not for elucidating phylogenetic relationships among Campylobacter isolates.